«Диэлектрлік материалдардың физикалық химиясы» пәнін оқу барысында студенттердің алған құзыреттіліктерін бағалаудың әдістемесі мен математикалық моделі - Pokholkov, Yu.; Muravlev, I.; Chervach М. (Хабаршы. Физика сериясы, 2022)
The article proposes a deterministic (not probabilistic) approach to assessing learning outcomes (LO), using a simple mathematical model for assessing the results of students’ learning within a course "Physical Chemistry of Dielectric Materials". Implementation of this approach involves a consistent shift, under the conditions of the assumptions made, from a general consistent concept of "quality of engineering education" to its components, detailing the learning outcomes, their quantitative assessment and, taking into account the required levels of learning outcomes, both for the main educational program in general, and for specific courses included in it. Principles for design and implementation of any course syllabus included in a study program are proposed and described. Both, the proposed algorithm for assessing student’s level of mastering of the expected competencies and the mathematical model allow for a quantitative assessment of the “knowledge” and “activity” components of education and, ultimately, a quantitative assessment of the level of student’s mastering of the planned competencies. The proposed approach, algorithm and mathematical model can be used by teachers for self-assessment and improvement of the educational process.